PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA GURU DIMODERASI SUPERVISI (Studi Kasus pada Guru-guru PNS SD di UPT Dinas pendidikan Kecamatan Gunem Kabupaten Rembang) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was conducted to examine the effect of the variables of teacher competence and Job Satisfaction to the performance of civil service teachers in the district education office UPT Gunem with supervision as a moderating variable.The population in this study was the civil servant teachers in elementary schools-District of Gunem, as many as 113 people. Data were collected using questionnaires and the returned and processed as many as 113 with SPSS 17. Test instruments used are validity and reliability. While model used is the coefficient of determination and test " F ". Test this hypothesis using regression analysis. Based on the results of the study concluded as follows : competence positive and significant effect on performance, Job Satisfaction does not affect the performance of teachers.Supervision doesn’t affect the performance of teachers. While the results of multiple regression testing moderation model suggests that supervision is able to moderate the effects of competenceand Job Satisfaction teacher. Keywords: competence, Job Satisfaction, supervision, Performance.